1988
DOI: 10.1207/s15327752jpa5201_12
|View full text |Cite
|
Sign up to set email alerts
|

Masculine Gender-Role Stress: Predictor of Anger, Anxiety, and Health-Risk Behaviors

Abstract: We suggest that male gender-role identification affects whether specific situations are appraised as stressful. A questionnaire was developed to measure masculine gender-role stress (MGRS). Correlational data and multiple regression were used to validate the MGRS scale as a measure of gender-related stress in men, and compare its predictive utility with Spence's commonly-used measure of masculinity. Findings indicate that stress appraisal is gender related, that is, men experience more masculine-role stress th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
202
1
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 230 publications
(209 citation statements)
references
References 8 publications
5
202
1
1
Order By: Relevance
“…This difference might be explained by the gender role associated with certain types of behavior. For example, research has shown that masculinity is related to health behavior such as regular exercise [47] smoking, and drinking [48,49]. Therefore, men might be more likely to engage in such behavior to emphasize their masculine gender role.…”
Section: Discussionmentioning
confidence: 99%
“…This difference might be explained by the gender role associated with certain types of behavior. For example, research has shown that masculinity is related to health behavior such as regular exercise [47] smoking, and drinking [48,49]. Therefore, men might be more likely to engage in such behavior to emphasize their masculine gender role.…”
Section: Discussionmentioning
confidence: 99%
“…The MGRS has good internal consistency (Cronbach Alphas = .90s) and good test-retest reliability (r=.93). In addition, the construct validity of the scale has been supported through correlations with two other measures of self-reported stress (e.g., the Multidimensional Anger Inventory; Siegal, 1986, and the "State" form of the State-Trait Anxiety Scale; Spielberger, Gorsuch, Lushene, Vagg, & Jacobs, 1983;Eisler, Skidmore, & Ward, 1988). Subjects responses to the MGRS were in exploratory analyses to examine the relation between male gender-role stress and intimate abusiveness.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, this study is based on the Masculine Gender Role Stress by Eisler, Skidmore, and Ward (1988) and the Feminine Gender Role Stress from Gillespie and Eisler (1992). These were adapted with cross-cultural and crosspopulation revisions according to experts' reviews and ratings to make them suitable for measuring gender role conflicts among college students in the context of China.…”
Section: Ways Of Self-injurious Behaviorsmentioning
confidence: 99%